Changes in Ukraine's legislation on the appointment of judicial-veterinary expertise and procedures of experts’ implication - Щербакова, Н. С.; Передера, С. Б.; Передера, Ж. О.; Щербаков, Є. А. (Scientific Progress & Innovations, 2018)
The article gives data about the analysis of changes in the criminal-procedural legislation of Ukraine in matters of legal grounds for conducting expert examinations and the procedure of involving experts in veterinary medicine. It was established that changes of the criminal procedure legislation in Ukraine on the legal grounds for conducting expert examinations and the procedure of involving experts in veterinary medicine show a systematic approximation of the normative and legal basis of Ukraine in the criminal process to international norms and standards and aim at achieving the maximum level of impartiality on the part of participants of the criminal legal proceedings.